CREATION, ADMINISTRATION AND ANALYSIS OF E-COURSES - Michal, MUNK; CERVENANSKA, Marcela (Trends in education, 2008)
The article presents publication edited by Pedagogical faculty of UKF in Nitra, entitled Creation, administration and analysis of e-courses.
Keywords: education; e-course; e-learning; creation of e-courses; administration of ecourses; analysis of e-courses; LMS; MS Class Server; SLK; MS SharePoint